Does the Behaviour of Commodity Stock Prices in India Constitute a Random Walk? - Jesudasan, Smita (SFIMAR Research Review, 2016)
Prices of underlying securities reveal informational content in an efficient market. The crux of the efficient market hypothesis [EMH] is that, at any point of time, stocks truly reflect in their market prices all the informational content. Such prices are fair to an extent that an investor cannot beat the market either through stock selection or market timing. The study is conducted to test whether the stock prices of companies engaged in the commodity sector confirm to a random walk approach. The random walk model states that companies ’stock prices are truly reflective of their fair values’. The daily returns of the Nifty Commodities Index and 30 companies listed on the National Stock Exchange are computed for the five-year calendar period from 1st January, 2011 to 31st December, 2015. Autocorrelation, Runs Test and GARCH Model (1,1) are the statistical tests used to empirically investigate, whether the price change at any point of time is influenced by the price changes that occurred during the preceding periods. The empirical evidence suggests that the stock prices of companies engaged in the commodity sector do not follow a random walk.